Consumption-based emission inventories in Nordic municipalities—a quest to develop support for local climate action - Sanderson, Hans; Hildén, Mikael; Saikku, Laura; Axelsson, Katarina; Pedersen, Anders Branth; Aamaas, Borgar (Frontiers in Climate, 2024)
Municipalities can play a large role in achieving global climate targets. Integrating a consumption-based perspective is key to being able to mitigate global emissions. We conducted a survey among municipality officials in four Nordic countries (Denmark, Finland, Norway, and Sweden) and held several workshops to deepen our understanding of municipalities' work to address consumption-based emissions. Findings show that less than half of the municipalities in the studied countries worked actively on measuring consumption-based emissions but that there is a broad interest in further developing GHG inventories that incorporate emissions from municipalities' own consumption as well as from citizens' consumption. Both expectations and challenges related to consumption-based inventories are remarkably similar across the four countries. A majority of the survey respondents perceived that the municipality could influence consumption-based emission from the municipality as a society by cooperating with residents and businesses. Similarly, information on consumption-based emissions was broadly identified as a key need to identify just and sustainable measures toward climate neutrality. The information generated was recognized by municipal employees to be useful for making better climate plans, optimizing their own operations' emission reductions, and helping residents and companies to reduce their emissions. We argue that it is essential that municipalities can base their actions on coherent and reliable information on consumption-based emissions that is comparable across municipalities and that can be connected to national tracking of emissions. This requires standardized methods and base-line data as not all municipalities can mobilize the needed human and financial resources to make their own inventories.